Preventing CRE exposure in endoscopy procedures. Issue 6 (30th November 2015) - Bartlett, Susan Elizabeth
Abstract : It is crucial to minimize the risk of exposing all patients to bacteria, but this article specifically discusses preventing hospital-acquired infections during an endoscopy.